2021
DOI: 10.21203/rs.3.rs-217480/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Faradarmani Consciousness Field Suppresses Alzheimer’s Disease Development in Both in Vitro and in Vivo Models of The Disease

Abstract: Background: Alzheimer’s Disease (AD) is one of the most common causes of dementia, imposing large financial and psychological burdens on nations worldwide. Thus, we are in dire need for new treatment strategies or drugs for this disease. The aim of this study is to investigate the effects of a novel non-pharmacological method in the treatment of Alzheimer’s disease, based on Taheri's Consciousness Field approach. This approach works at the level of cellular and molecular processes and is tested in neuronal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The sera of each group was mixed (pooled) at each stage of blood sampling. In In previous studies, the effects of the TCFs on MCF7 cancer cell line (Taheri et al, 2020a), Alzheimer's disease rat models (Taheri et al, 2021b), spatial memory, and avoidance behavior of a rat model of Alzheimer's disease (Taheri et al, 2021c), wheat plant (Torabi et al 2020), bacterial population growth (Taheri et al, 2021d), viral growth (Taheri et al 2021a), and the electrical activity of the brain during Faradarmani in the Faradarmangars population have been investigated (Taheri et al, 2020b).…”
Section: Serum Neutralization and Elisa Testsmentioning
confidence: 99%
“…The sera of each group was mixed (pooled) at each stage of blood sampling. In In previous studies, the effects of the TCFs on MCF7 cancer cell line (Taheri et al, 2020a), Alzheimer's disease rat models (Taheri et al, 2021b), spatial memory, and avoidance behavior of a rat model of Alzheimer's disease (Taheri et al, 2021c), wheat plant (Torabi et al 2020), bacterial population growth (Taheri et al, 2021d), viral growth (Taheri et al 2021a), and the electrical activity of the brain during Faradarmani in the Faradarmangars population have been investigated (Taheri et al, 2020b).…”
Section: Serum Neutralization and Elisa Testsmentioning
confidence: 99%
“…of TCFs by observing their effects. The nature of T-Consciousness and what it is will not be ad-the mind and memory of matter and their relation to the T-Consciousness, etc.In previous research, the effects of the TCFs on MCF7 cancer cell line(Taheri et al, 2020a), Alzheimer's disease rat models(Taheri et al, 2021b), spatial memory, and avoidance behavior of a rat model of Alzheimer's disease(Taheri et al, 2021c), tolerance of Triticum aestivum L. under salinity stress(Torabi et al, 2020), bacterial activity of the brain during Faradarmani in the Faradarmangars population(Taheri et al, 2020b) have been observed.In this study, the effects of TCFs (A, B, and C) are evaluated separately to investigate the infec--cluding bread, dairies, meats, and fruits.MATERIAL AND METHODSApplication of Taheri Consciousness FieldsTCFs were applied to the samples according to the protocols regulated by COSMOintel research center (www.COSMOintel.com nection to the CCN to utilize TCFs can be placed through the COSMOintel website in the "Assign Aneveryone at no cost. In order to study and experience this Connection, the researchers can register on the website at any time and in order to report the experiment to the COSMOintel research center.…”
mentioning
confidence: 99%
“…of TCFs by observing their effects. The nature of T-Consciousness and what it is will not be ad-memory of matter and their relation to the T-Consciousness, etc.In previous research, the effects of the TCFs on MCF7 cancer cell line(Taheri et al, 2020a), Alzheimer's disease rat models(Taheri et al, 2021b), spatial memory, and avoidance behavior of a rat model of Alzheimer's disease(Taheri et al, 2021c), wheat plant(Torabi et al, 2020), bacterial population growth(Taheri et al, 2021d), viral growth(Taheri et al, 2021a), and the electrical activity of the brain during the Faradarmani Connection in the Faradarmangars population(Taheri et al, 2020b) have been investigated. This study aimed to investigate the effects of two TCFs (A and TCID50 were used for the evaluation of virus survival and infectivity.…”
mentioning
confidence: 99%